Impacto de la deuda externa e inversión extranjera directa en el crecimiento económico a nivel mundial periodo 1985-2019 - Cueva Jiménez, Alex Miguel (2023)
In recent years, economic growth has shown a gradual slowdown. In 2019 the growth of economies was 2.6% which presents a decrease of 0.7% compared to 2018, whereby it is utmost importance to generate solutions. The present research objective is evaluating the impact of the external debt and foreign direct investment on the economic growth in 53 countries worldwide in the period 1985-2019. The data information is taken from the World Bank (2022), which corresponds to panel data. In order to get the research´s objective a Generalized Least Squares (GLS) model and short and long run estimators (AMG, CCE-MG, FMOLS and DOLS) were used. The results indicate that the external debt generates economic degradation and hinders economic growth in the long term, while foreign direct investment potentiate productive sectors, helping to stimulate the generation of value added. It also was proven the existence of bidirectional causality between external debt and foreign investment towards global growth. Taking into consideration the results, policies should be generated to direct foreign financing towards productive sectors, and private companies should be given a leading role and guidelines should be created in which national interests and foreign investors coincide.